Advanced digital subtraction angiography and MR fusion imaging protocol applied to accurate placement of flow diverter device. (14th January 2015) - Faragò, Giuseppe; Caldiera, Valentina; Tempra, Giovanni; Ciceri, Elisa
Abstract : In recent years there has been a progressive increase in interventional neuroradiology procedures, partially due to improvements in devices, but also to the simultaneous development of technologies and radiological images. Cone beam CT (Dyna-CT; Siemens) is a method recently used to obtain pseudo CT images from digital subtraction angiography (DSA) with a flat panel detector. Using dedicated software, it is then possible to merge Dyna-CT images with images from a different source. We report here the usefulness of advanced DSA techniques (Syngo-Dyna CT, three-dimensional DSA iPilot) for the treatment of an intracranial aneurysm with a flow diverter device. Merging MR and Dyna-CT images at the end of the procedure proved to be a simple and rapid additional method of verifying the success of the intervention.